Microfinance as poverty-shame debt. Issue 2 (1st November 2019) - Engel, Susan; Pedersen, David
Abstract : In an excellent anthropological study of microfinance in Bangladesh, Karim (2008: xviii) argues that it operates as 'an economy of shame'. That is to say, microfinance is not the benign tool for financial inclusion and empowerment that mainstream development organisations proclaim. Rather, it unintentionally (perhaps) but nevertheless actively deploys shaming techniques in order to maximise loan repayment rates. Karim, however, does not employ an explicit analysis of shame; instead she emphasises its disciplining power for rural women in Bangladesh. Our article builds on this insight but applies a specific psychosocial approach to shame that critically examines a number of the emotion's harmful practices and outcomes, especially when deployed within microfinance practice. It highlights that microfinance personalises and socialises people's debt relations, making them a matter for group concern, but that at the same time money-debt's impersonalising nature results in coercive and disciplinary actions that would otherwise be seen as intolerable. We demonstrate how the active shaming of microfinance participants all too often degenerates into human rights abuses, including violence. The shame of debt and the active shaming that facilitates microfinance's high repayment rates harms the psychosocial wellbeing of those being shamed as well as their families, and can be linked to a range of concerning outcomes including self-harm and suicide. To conclude, we explore whether the coercion by shame and shaming of microfinance may be linked to its growing use in other areas of development programming.